Introduksi Tanaman Indigofera Pada Sistem Agroforestry Sebagai Sumber Pakan Ternak KTH di Desa Anabanua Kabupaten Barru - Muhammad Kadir; Erna Halid; Andi Ayu Nurnawati; Syatrawati; Nildayanti; Henny Poerwanty (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The potential of Anabanua Village as one of the villages given access to Community Forest Management (CFM) to cultivate the Agroforestry system and also Livestock Development, has a problem of providing natural food sources. The utilization of elephant grass is no longer sufficient, especially in the dry season which is prone to drought. Feed plants that are able to substitute and enrich (diversify) existing feed source plants are needed. Indigofera sp is a food crop that is rich in benefits and has the main advantage of being tolerant to drought stress, so activities are carried out to provide knowledge and skills and obtain added value by planting Indigofera plants in the community Agroforestry system. Activities are carried out to provide the ability to multiply, plant and maintain Indigofera plants as a source of food in the form of counseling and training as well as direct planting of Indigofera plants on the land of forest farmer groups (FFG).